Fantastic beasts : the crimes of Grindelwald [videorecording (DVD)] - Yates, David, 1963-; Redmayne, Eddie, 1982-; Waterston, Katherine; Fogler, Dan (Warner Bros. Entertainment, 2018)
Albus Dumbledore enlists the help of his former student Newt Scamander to thwart the attempts of dark wizard Grindelwald to achieve worldwide wizard supremacy and domination.